The Role of Culinary Destination Image and Culinary Memory on Culinary Destination Loyalty - Arifin Djakasaputra; Juliana Juliana; Amelda Pramezwary; Ira Brunchilda Hubner; Gunawan Prabowo; Rocky Nagoya (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Culinary tourism is a trip with a typical and enjoyable eating and drinking experience for local residents, this culinary tour has long been identified as a key element that contributes to the competitiveness of a destination. Based on the theory of motivation, opportunity, ability (MOA), this study investigates to test and analyze the influence of Motivation, Time pressure, Prior knowledge mediated by culinary destination image and Culinary Memory on culinarian destination loyalty. Tourists who visit culinary tours are the subject of this study. This study involved 200 respondents. This quantitative research uses surveys. In this study, the data collection tool is an online questionnaire that is distributed to Indonesian tourists visiting culinary attractions. The data collection was carried out using purposive and non-probability sampling methods based on the criteria of tourists who have visited the culinary sights once a year. PLS-SEM is used to analyze data. The results show that all the hypotheses are supported. Motivation, Time pressure, Prior knowledge, culinary destination image is presented as independent variables, while Culinary Memory serves as mediation variables and culinarian destination loyalty as dependent variables. Implications of this study are conceptual models that effectively explain the culinary tourism with all the constructions that have a positive impact on the gastronomic destination loyalty. It can be concluded that the culinary destination image plays a role in shaping the visitor's desire to make a re-purchase.